History of relations of Kazakhstan with the organization of islamic cooperation in issues of gender equality (Journal of history, 2021)
The article provides a historical analysis of the development of relations between Kazakhstan and the OIC. The Organization of Islamic Cooperation unites Muslim countries and aims to increase its authority and influence in the modern world. Today the Islamic world is aware of its lagging behind the indicators of the Western community in the economic, cultural, and civilizational dimension. Despite the fact that all OIC states are members of the UN, their internal policies are criticized on many issues. In particular, this concerns human rights, gender equality, and discrimination against women.Kazakhstan is a secular state in which dozens of confessions peacefully coexist and women enjoy equal rights with men. Therefore, having joined the OIC, our country began to pay great attention to human rights and gender aspects. In a sense, we can say that thanks to the efforts of the Republic of Kazakhstan, positive changes began to occur in the gender development of the OIC member countries. The increased authority and influence of Kazakhstan was appreciated by the members of the organization, who elected him to the post of chairman in 2011.Key words: United Nations, Millennium Declaration, Organization of the Islamic Conference, human rights, gender equality.